2019
DOI: 10.3390/ani9110952
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Single Nucleotide Polymorphisms in Porcine MAOA Gene Associated with Aggressive Behavior of Weaned Pigs after Group Mixing

Abstract: Simple SummaryMonoamine Oxidase A (MAOA) gene had been reported as a candidate gene of aggressive behavior in several species. In the present study, the most aggressive and docile weaned pigs in each pen after group mixing were selected to identify single nucleotide polymorphisms in porcine MAOA gene associated with aggressive behavior. Constructs containing variable lengths of truncated porcine MAOA promoter were used to determine the promoter activity by a dual luciferase reporter system. The core promoter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Of interest is the group of genes associated with behaviour that were grouped into two clusters by the protein–protein interaction analysis (Figure S1). On OAR27 (between 31.28 and 32.18 Mb) map MAOA and MAOB genes, both associated with aggressive behaviour in cattle, sheep, and pigs (Alvarenga et al., 2021; Chen et al., 2019; Eusebi et al., 2020). The MAOB gene was also related to dairy temperament in cattle (Macleod et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is the group of genes associated with behaviour that were grouped into two clusters by the protein–protein interaction analysis (Figure S1). On OAR27 (between 31.28 and 32.18 Mb) map MAOA and MAOB genes, both associated with aggressive behaviour in cattle, sheep, and pigs (Alvarenga et al., 2021; Chen et al., 2019; Eusebi et al., 2020). The MAOB gene was also related to dairy temperament in cattle (Macleod et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As far as aggressive behavior is concerned, whole genome studies are scarce in pigs [ 80 , 81 ] as well as exploration of candidate genes or genomic markers [ 82 , 83 , 84 , 85 , 86 ]. Wurtz et al [ 81 ] evidenced only one region on chromosome 11 for skin lesions that need to be confirmed.…”
Section: Perspectivesmentioning
confidence: 99%
“…The promoter is a key component of genes, controlling the initiation location and expression abundance of the gene [ 53 ]. We demonstrated that the core promoter region of DRD2 gene is located in a transcription activator binding region from −2212 to −1127 bp.…”
Section: Discussionmentioning
confidence: 99%